Social and Intellectual Origins of Neo-Ottomanism: Searching for a Post-National Vision - Yavuz, M. Hakan (Die Welt des Islams, 2016)
This article will unpack the intellectual and sociopolitical conditions under which the idea of neo-Ottomanism was formulated, by focusing on the following questions: What is neo-Ottomanism, who constructed the term, and for what purpose? What aspects of the Ottoman legacy have been incorporated in the ‘self’ definition of a new Turkey? Is this shift temporary or rooted in a more far-reaching transformation of Turkish society that will shape future sociopolitical choices? The article examines the intellectual origins of the term ‘neo-Ottomanism’ by examining the role of cultural entrepreneurs, such as Yahya Kemal and Ahmet Hamdi Tanpınar, along with the interactions among social factors, in the search for a new ‘old’ identity of Ottomanism by reimagining the Ottoman past. It seeks to provide a historical and sociological perspective of the process of reconfiguring the past, and especially its implications in domestic and foreign policy. Due to the oppressive nation-building project of the Kemalist regime, literature, art, music, and poetry became alternative sites for preserving, updating, and reconstructing the Ottoman memory. After explaining the formation of neo-Ottoman discourse in the 1990s, the article will address the debate about the politics of identity under the Justice and Development Party (JDP).